2013
DOI: 10.1002/acr.21893
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Magnetic Resonance Imaging Reference Criterion for Defining a Positive Sacroiliac Joint Magnetic Resonance Imaging Finding in Spondyloarthritis

Abstract: Using this MRI reference criterion, the cutoff for the number of affected SI joint quadrants needed to reach a predefined specificity of >0.90 was >2 for bone marrow edema (BME) in both cohorts and >1 for erosion in both cohorts, and the BME and/or erosion lesions increased sensitivity without reducing specificity. Conclusion. This data-driven study using 2 inception cohorts and comparing clinical and MRI-based classification supports the case for including both erosion and BME to define a positive SI joint MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 20 publications
3
55
2
1
Order By: Relevance
“…Among patients with bone marrow oedema at the SIJ, we found a significantly higher prevalence of erosions in patients fulfilling the ASAS criteria for SpA (41 %) compared to those who did not fulfil the criteria (20 %). These results support inclusion of erosions in the definition of a 'positive MRI finding' for the classification of SpA, as previously proposed [38].…”
Section: Discussionsupporting
confidence: 82%
“…Among patients with bone marrow oedema at the SIJ, we found a significantly higher prevalence of erosions in patients fulfilling the ASAS criteria for SpA (41 %) compared to those who did not fulfil the criteria (20 %). These results support inclusion of erosions in the definition of a 'positive MRI finding' for the classification of SpA, as previously proposed [38].…”
Section: Discussionsupporting
confidence: 82%
“…They reported data from two cohorts and found that ≥1 erosion (both cohorts) and ‘≥12/≥9 fatty lesions’ (cohort A/B) yielded a specificity of ≥90.0%. When looking at lesion combinations they found ‘≥12/≥11 fatty lesions and/or erosions’ (cohort A/B) to be most specific for axSpA 20. There is a difference in study design compared with our study.…”
Section: Discussionmentioning
confidence: 56%
“…19–31 Three studies reported SE (0.73–0.9) and SP (0.9–0.97) for SI joint BME on MRI in established AS 22 23 25. Wick et al 26 reported an SE of 0.11 and an SP of 0.93 for MRI SI joint erosions for diagnosis of AS, while Weber et al 25 reported that the combined features of SI joint erosion and/or BME increased SE to 0.98–0.96 compared with BME alone (0.91–0.83) without reducing SP and the area under the curve for diagnosis of AS. Heuft-Dorenborsch et al found that initial assessment of structural changes by radiography followed by MRI assessment of inflammation with negative radiography gives the highest returns for detecting involvement of the SI joint in patients with recent IBP 27.…”
Section: Resultsmentioning
confidence: 99%